PENDAMPINGAN PEMBANGUNAN RUMAH SUSUN KEMENSOS BBRSPDF PROF. DR. SOEHARSO, KOTA SURAKARTA - Namira Farah Amitra (Jurnal Vokasi Teknik Sipil, 2024)
The Magang dan Studi Independen Bersertifikat program (MSIB) is an internship program held by the government through the Ministry of Education and Culture so that students gain experience in the world of work in a professional manner. The Directorate General of Housing under the auspices of the Ministry of Pekerjaan Umum dan Perumahan Rakyat (PUPR) has also opened an apprenticeship program with one of them as Assistant for Flats Development. The Directorate of Flats in the 2022 strategic plan plans an assistance program for the construction of flats of 51,340 units by 2024. Therefore, students are invited to directly participate in the apartment development assistance program. Student participation in this program is assisting the construction of flats as Construction Supervisor Assistants or Project Management Assistants spread across 7 provinces in Indonesia. This internship program will provide many benefits such as increasing knowledge regarding assistance in the construction of flats, procurement of construction services, project management and other knowledge, especially in the field of construction.